Lessons of the Crusades and the Mongol hordes Salahuddin al-Ayyubi and his successors - Nadwi, Syed Abul Hasan Ali (Islamic Book Trust, 2006)
The aggression unleashed on the Muslim world today by its enemies combines the elements and spirit of both the Crusades and the invasion of the mongol hordes the two tragedies in history which almost wiped out Islam. We will be struck with the parallel we find in the conditions just preceding the two catastrophes mentioned in this book and the social religious and political conditions prevailing in the present day Muslim world. The readers may draw thier own conclusion as to the reasons of present day humiliation and sufferings of the Muslim Ummah in spite of the fact the Muslim world has been blessed with the most strategic land mass and natural resources.